What works in foster care? key components of success from the Northwest Foster Care Alumni Study - Pecora, Peter J. (New York ; Oxford : Oxford University Press, 2009)
The Northwest Foster Care Alumni Study found that quality foster care services for children pay big dividends when they grow up. Key investments in highly trained staff, low caseloads and robust complementary services can dramatically reduce rates of mental disorders and substance abuse. This book offers a model foster care programme.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Foster children -- United States; Foster home care -- United States